2023
DOI: 10.3390/ijms241511922
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Cells and Molecules of Innate Immunity in Alzheimer’s Disease

Abstract: The inflammatory response that marks Alzheimer’s disease (neuroinflammation) is considered a double-edged sword. Microglia have been shown to play a protective role at the beginning of the disease. Still, persistent harmful stimuli further activate microglia, inducing an exacerbating inflammatory process which impairs β-amyloid peptide clearance capability and leads to neurotoxicity and neurodegeneration. Moreover, microglia also appear to be closely involved in the spread of tau pathology. Soluble TREM2 also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 175 publications
0
7
0
Order By: Relevance
“…sTREM2 in plasma may be associated with other diseases, such as white matter lesions (Tsai et al, 2021). Although sTREM2 can serve as a potential biomarker for AD, sTREM2 levels alone may not be sufficient for an accurate diagnosis of AD, and sTREM2 in CSF is complexly associated with other AD biomarkers (Tamburini et al, 2023). Studies have shown that the levels of sTREM2 are positively correlated with the levels of classical CSF markers total Tau (t-Tau) and phosphorylated-Tau (p-Tau), but not with the concentration of CSF Aβ 42 (Heslegrave et al, 2016;Piccio et al, 2016).…”
Section: Ligand Main Results Refmentioning
confidence: 99%
See 1 more Smart Citation
“…sTREM2 in plasma may be associated with other diseases, such as white matter lesions (Tsai et al, 2021). Although sTREM2 can serve as a potential biomarker for AD, sTREM2 levels alone may not be sufficient for an accurate diagnosis of AD, and sTREM2 in CSF is complexly associated with other AD biomarkers (Tamburini et al, 2023). Studies have shown that the levels of sTREM2 are positively correlated with the levels of classical CSF markers total Tau (t-Tau) and phosphorylated-Tau (p-Tau), but not with the concentration of CSF Aβ 42 (Heslegrave et al, 2016;Piccio et al, 2016).…”
Section: Ligand Main Results Refmentioning
confidence: 99%
“…Because TREM2 can recognize a variety of ligands closely related to AD and is one of the key regulators of microglial phenotype switching, it plays an important role in the progression of neuroinflammation (Tamburini et al, 2023). Therefore, TREM2 has been extensively studied as a potential AD biomarker.…”
Section: Trem2 Is a Potential Ad Biomarkermentioning
confidence: 99%
“…By releasing cytokines that can be pro-inflammatory or anti-inflammatory, and by phagocytosing or clearing harmful substances, immune cells can combat infection and injury, which affects neuroinflammation ( 48 ). Lcn-2 can influence the activation state of immune cells by binding to 24p3R and modulating the production and release of cytokines, communication molecules between cells.…”
Section: The Signaling Pathways and Mechanisms Of Lcn-2 In The Regula...mentioning
confidence: 99%
“…It is predominantly attributed to central nervous system (CNS) immune cell dysfunction, particularly involving astrocytes and microglia. A large number of studies have explored the impact of sex on neuroinflammation in AD ( Guillot-Sestier et al, 2021 ; Singh, 2022 ; Cui et al, 2023 ; Tamburini et al, 2023 ). Specifically, one study that explored sex differences in microglia using post-mortem tissue from male and female AD patients revealed a noteworthy increase in the count of dystrophic microglia in AD females ( O'Neill et al, 2022 ).…”
Section: Sex Differences In Alzheimer’s Diseasementioning
confidence: 99%